Chapter Aria di casa. Du Bos e il carattere delle piante-nazione - MAZZA, EMILIO (Studi e saggi, 2020)
Plants-Nations have very different characters in different countries or in different ages in the same country; like wines, in every terroir they have a particular taste and always preserve it, though some years are better than others. Everything depends upon the air and its qualities. It is a home air, but it is not always the same. National characters are the product of a (changeable) balance between identity and diversity, permanent general elements and variations in time. Jean-Baptiste Du Bos' Réflexions critiques sur la poésie et sur la peinture, first published in 1719, attempt to keep this balance and present themselves as an indispensable reading for those who want to discuss national characters and their causes even in 1748, when Montesquieu published the Esprit des lois and Hume Of National Characters.